Revisiting Vh(→ b b ¯ $$ b\overline{b} $$ ) at the LHC and FCC-hh - Fady Bishara; Philipp Englert; Christophe Grojean; Giuliano Panico; Alejo N. Rossia (Journal of High Energy Physics, 2023)
Abstract Diboson production processes provide good targets for precision measurements at present and future hadron colliders. We consider Vh production, focusing on the h → b b ¯ $$ b\overline{b} $$ decay channel, whose sizeable cross section makes it accessible at the LHC. We perform an improved analysis by combining the 0-, 1- and 2-lepton channels with a scale-invariant b-tagging algorithm that allows us to exploit events with either a boosted Higgs via mass-drop tagging or resolved b-jets. This strategy gives sensitivity to 4 dimension-6 SMEFT operators that modify the W and Z couplings to quarks and is competitive with the bounds obtained from global fits. The benefit of the h → b b ¯ $$ b\overline{b} $$ decay channel is the fact that it is the only Vh channel accessible at the LHC Run 3 and HL-LHC, while at FCC-hh it is competitive with the effectively background-free h → γγ channel assuming ≲ 5% systematic uncertainty. Combining the boosted and resolved categories yields a 17% improvement on the most strongly bounded Wilson coefficient at the LHC Run 3 with respect to the boosted category alone (and a 7% improvement at FCC-hh). We also show that, at FCC-hh, a binning in the rapidity of the Vh system can significantly reduce correlations between some EFT operators. The bounds we obtain translate to a lower bound on the new physics scale of 5, 8, and 20 TeV at the LHC Run 3, HL-LHC, and FCC-hh respectively, assuming new-physics couplings of order unity. Finally, we assess the impact of the Vh production channel on anomalous triple gauge coupling measurements, comparing with their determination at lepton colliders.